Flexural failure properties of fiber-reinforced hybrid laminated beam subject to three-point bending - Tefera, Getahun; Adali, Sarp; Bright, Glen (Scientific reports, 2024)
The present study investigates the flexural failure properties of a hybrid laminate beam subjected to three-point bending. A symmetrically laminated hybrid beam is constructed using high-strain and inexpensive glass fibre on the top layers and low-strain and expensive carbon fiber on the middle layers. Classical lamination plate theory is used to find the stress and strain distribution that occurs due to the bending moment on the compressive side. The theoretical failure limits of the laminated hybrid beam are analyzed considering the targeted span-to-depth ratios, volume fractions of the fibers and hybrid ratios using the Tsai-Wu failure criterion and Matlab codes. Using the graph of failure index versus hybrid ratios, the minimum thickness of carbon fiber needed for the delay of failure and cost efficiency of the laminated hybrid beam is identified by applying the linear interpolation method. The numerical results indicate that the failure index increases with the increasing loading span and decreases when the volume fraction of fiber increases. In particular, the placement of glass fiber on the top layer of the laminated hybrid beam might have contributed to obtaining higher strains and curvatures before the catastrophic failure properties of carbon fiber. The flexural stiffness of the laminates is found to increase when the hybrid ratio increases. Overall, it is noted that the theoretical analysis is one method that is less time-consuming and cost-effective than other alternative approaches, such as finite element methods and experimental tests to estimate the minimum thickness of high-stiffness and the expensive material needed to maintain the strength and stiffness of the hybrid composite structures over long periods.